Elements of an Educational Environments Empowering Students to Perform Reasoning on Their Career Choice - Surgėlienė, Jurgita; Bankauskienė, Nijolė (Pedagogika, 2015)
Despite the abundance of career education interventions and information on career opportunities, in reality, the search for information process is not necessarily performed very thoroughly, and thus persons, choosing a profession, do it in the simplest way, being unable to properly explain their decisions afterwards (Philips, Jome, 2005). It has been noticed (Wu, 2002) that students tend to identify their ideas as reasoning. Instead of proper reasoning on their decision, they tend to choose intuitively, based on their feelings. A certain environment is required in order to empower a student to perform reasoning. An environment providing students with conditions for developing the necessary skills and enabling them to implement these skills. It is critical to discover to what are the elements of an educational environment empowering students to perform reasoning on their career choice? The aim of this work is to reveal the elements of an educational environment empowering students to perform reasoning on their career choice. Objectives: 1. To reveal the essence of the elements of an educational environment empowering students to perform reasoning on their career choice. 2. To point out the elements of an educational environment empowering students to perform reasoning on their career choice in general secondary school. The main elements of the educational environment empowering students to perform reasoning on their career choice are: empowering conditions present at educational institution, engaged subjects from school community, educational technologies, orientation to students’ preparedness to perform reasoning on their career choice, peculiarities of activities are necessary, educational environment of relatives.